2000
DOI: 10.1152/jn.2000.83.4.2093
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Responses and Movement Strategies During Stumbling Over Obstacles

Abstract: Although many studies have investigated reflexes after stimulation of either cutaneous or proprioceptive afferents, much less is known about responses after more natural perturbations, such as stumbling over an obstacle. In particular, the phase dependency of these responses and their relation to the stumbling behavior has received little attention. Hence response strategies during stumbling reactions after perturbations at different times in the swing phase of gait were studied. While subjects walked on a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
171
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(194 citation statements)
references
References 38 publications
21
171
2
Order By: Relevance
“…Both aspects of the control of the responses after a trip could be affected in older subjects, resulting in inadequate recovery after tripping. The rate at which the recovery limb is activated was addressed by other authors (Eng et al 1994;Schillings et al 2000). One should bear in mind, however, that the support limb contributes to accelerating the recovery limb relative to the upper body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both aspects of the control of the responses after a trip could be affected in older subjects, resulting in inadequate recovery after tripping. The rate at which the recovery limb is activated was addressed by other authors (Eng et al 1994;Schillings et al 2000). One should bear in mind, however, that the support limb contributes to accelerating the recovery limb relative to the upper body.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that most elevating strategies were performed after a trip initiated in early swing, whereas most lowering strategies were performed when the trip was initiated in late swing, according to the literature (Eng et al 1994;Schillings et al 2000). Still, in young as well as in older subjects, around mid-swing either of these strategies could be elicited.…”
Section: Timing and Sequencing Of Muscle Activationmentioning
confidence: 94%
See 2 more Smart Citations
“…According to Schillings and colleagues [SvWMD00], the choice of strategies depends on the timing of the collision with an obstacle. When a collision is caused in early swing (5-25% of stride duration in normal walking), the elevating strategy is chosen.…”
Section: Biomechanical Principles Of Balance Recovery Responses To Tripsmentioning
confidence: 99%